Comparative study of three different fixation techniques for the treatment of Neer type IIb distal clavicle fractures: A retrospective cohort study - Liu, Zhi-Qing; Zhang, Ming-Shi; Zhou, Zi-Fei; Zhang, Lei; Zheng, Long-Po (Frontiers in Surgery, 2023)
Background Recently, locking plate combined with a suture button was applied for distal clavicle Neer Type IIb fractures. However, to our knowledge, there is limited information on clinical outcomes about locking plate combined with a suture button in the treatment of Neer Type IIb distal clavicle fractures．The aim of this study is to compare the outcomes among three different fixation techniques for the treatment of Neer Type IIb distal clavicle fractures. Methods We performed a retrospective cohort study of 53 patients with Neer type IIb distal clavicle fractures who were treated with hook plate (HP group, 16 patients), locking plate alone (LP group, 18 patients) or locking plate with suture button (LPSB group, 19 patients) in our hospital from March 2014 to August 2019. The clinical and radiological outcomes were evaluated including union time, postoperative complications, function of shoulder joint. Results The follow-up period was at least 2 years for all patients. All patients achieved bone healing in LPSB group at the final follow-up. No significant differences were observed including age, gender, side, time to surgery, duration of surgery and the mean follow-up period among the three groups (p> 0.05). Union time was shorter in LPSB group than that in other two groups (p< 0.05). Postoperative complications were lower in LPSB group than those in other two groups (p< 0.05). The visual analog scale score (VAS), Constant–Murley score (CMS) in LPSB group were better than those in other groups at 3 months and 6 months after the operation (p< 0.05). Conclusion Compared with HP and LP alone, LPSB yields better clinical outcomes and lower complication rates in the treatment of Neer IIb distal clavicle fractures.